Kyrgyz Republic : Integrated State-Owned Enterprises Framework Assessment - World Bank (World Bank, Washington, DC, 2021)
Notwithstanding its significant downsizing due to the country´s transition from a planned to a market economy, the public sector in Kyrgyz Republic still owns one hundred thirty-six SOEs, with the largest ones operating in strategic and economically important sectors. The main objective of this integrated state-owned enterprises framework assessment (iSOEF) is to analyze the economic and fiscal impact of the Kyrgyz state-owned enterprise (SOE) portfolio, and identify ways to strengthen its performance and corporate governance. This report describes the landscape and main characteristics of the SOE portfolio in the Kyrgyz Republic, provides an assessment of main fiscal costs and risks of the SOEs with a focus on energy sector SOEs, and analyzes the corporate governance and financial reporting frameworks and practices applied by Kyrgyz SOEs.